2007
DOI: 10.1111/j.1532-849x.2007.00246.x
|View full text |Cite
|
Sign up to set email alerts
|

“All‐on‐Four” Immediate Function Concept and Clinical Report of Treatment of an Edentulous Mandible with a Fixed Complete Denture and Milled Titanium Framework

Abstract: The "All-on-Four" concept-tilting the distal implants in the edentulous arches improves the prosthetic support-increases the inter-implant distance and provides better implant anchorage in the bone by using longer implants. Computer milling of a solid block of titanium also provides frameworks with improved fit and fewer technical challenges than conventional cast or noncast approaches. This clinical report describes a method of restoring an edentulous mandible with the "All-on-Four" immediate function concept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
29
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 14 publications
6
29
0
1
Order By: Relevance
“…[39][40][41][42][43] The results of this study are in harmony with these studies. However, it has a little effect in reducing the stresses occurring in the crest hills and supportive tissues around the implants against the occlusal loads.…”
Section: Discussionsupporting
confidence: 84%
“…[39][40][41][42][43] The results of this study are in harmony with these studies. However, it has a little effect in reducing the stresses occurring in the crest hills and supportive tissues around the implants against the occlusal loads.…”
Section: Discussionsupporting
confidence: 84%
“…Vague documentation of results Jensen et al 52 Case report Bedrossian 53 Zygoma implants Khatami and Smith 54 Case report Bedrossian 55 Zygoma implants Krekmanov et al 11 Number of implants/study design Butura et al 56 Case report Menini et al 33 Literature review Cannizzaro et al 57 Study design/no survival rates reported 64 Case report, zygoma implants Penarrocha-Oltra et al 65 Literature review Graves et al 66 Zygoma implants Pomares 67 Number of implants Graves et al 68 Zygoma implants Rosen and Gynther 69 Number of implants Jensen et al 70 Case report Wu et al 71 Language 74 Number of implants/study design Penarrocha-Oltra et al 75 Not tilted/study design Astrand et al 76 Number of implants/overdentures Pieri et al 77 Number of implants Eccelente et al 78 Removable prosthesis Pomares 79 Number of implants Ekelund et al 80 Number of implants Pomares 67 Number of implants Friberg and Jemt 81 Not tilted Romanos et al 82 Removable prosthesis Heschl et al 83 Removable prosthesis Wolfinger et al 84 Number of implants/study design Li et al 85 Number of implants/study design Wu et al 71 Language…”
Section: Outcome Measurementsmentioning
confidence: 99%
“…9 The success of using 4 implants to support the fixed complete prosthesis, originally described as the ''all-on-4 technique,'' has also been described in the literature by such authors as Maló et al, 6 Ferreira et al, 12 and Khatami and Smith. 13 The distal inclination of the implants is to reduce deleterious effects of the cantilever. In this connection, the studies of Sertgö z 9 using the finite element method showed that higher stresses were also concentrated on the distal implant on the same loading side and the presence of the cantilever increased stress around implants.…”
Section: Discussionmentioning
confidence: 99%